Paraneoplastic erythroderma: unusual presentation secondary to diffuse large B cell lymphoma. Issue 5 (30th May 2019) - Lim, Puo Nen; Fox, Christopher P; Pammi, Manjula; Patel, Anand
Abstract : A 34-year-old HIV-positive man presented in clinic with generalised erythroderma, having been lost to follow-up for the previous 3 years. He was CD4 lymphopenic (100×10 6 /L) and was antiretroviral therapy naive. Initial histology from a skin punch biopsy was non-specific and he was treated with topical steroids and emollients for a suspected eczema. However, the erythroderma worsened with development of cervical lymphadenopathy and significant weight loss over a 6-week period. An incisional biopsy from the left tonsil confirmed a diagnosis of diffuse large B-cell lymphoma. The erythroderma was considered to be a paraneoplastic skin phenomenon. The patient received rituximab, cyclophosphamide, doxorubicin hydrochloride, vincristine and prednisolone (CHOP) immunochemotherapy with gradual but complete resolution of the erythroderma. Paraneoplastic dermatoses can manifest as first clinical sign of underlying malignancy, heralding a cancer diagnosis. This is particularly important in people living with HIV given the increased incidence of malignancy in this patient group.